PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN INTENSI PROSOSIAL SISWA KELAS X SMA NEGERI 10 PEKANBARU TAHUN AJARAN 2013 2014 - IinInnayah IinInnayah; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study aimed to examine the effect of group guidance on the increase prosocial intentions tenth grade student’s of SMA Negeri 10 Pekanbaru Academic Year 2013/2014. Methods used in this study is the method of quasi experiment, using one group pretest - posttest design. And sampling in this study 25% of the total population using Porposive Sampling Technique, group guidance used as one way increasing prosocial intentions of student through several treatments. The hypothesis of this study is that there is difference in prosocial intentions of students before and after participating in group guidance activities at 5% error level. From the results of the processing are used by researchers, the test results obtained by the correlation of the two variables of group guidance activities contributing to the improvement of student’s prosocial intentions by 61%. And then based on the results of the t test of t greater than t table (11.96> 2,064). Based on the above it can be concluded that the group guidance activities were well prepared as a highly effective intervention technique for the improvement of prosocial intentions of student’s in the school. Furthermore, researchers recommend to the supervising teacher or school counselor in order to carry out the activities of a group guidance to students of class XI and XII in order to increase student’s prosocial intentions or other positive behaviors.Keywords: Intention Prosocial, Guidance Group